2020
DOI: 10.3847/1538-4357/ab9e71
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Study of Volatile Chemistry in Protoplanetary Disks

Abstract: The volatile composition of a planet is determined by the inventory of gas and ice in the parent disk. The volatile chemistry in the disk is expected to evolve over time, though this evolution is poorly constrained observationally. We present ALMA observations of C 18 O, C 2 H, and the isotopologues H 13 CN, HC 15 N, and DCN towards five Class 0/I disk candidates. Combined with a sample of fourteen Class II disks presented in Bergner et al. (2019b), this data set offers a view of volatile chemical evolution ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 116 publications
11
50
2
Order By: Relevance
“…The derived C 17 O abundances are thus within a factor of 5 of the ISM abundance, suggesting that no substantial processing has happened, as observed for Class II disks where the CO abundance can be 2 orders of magnitude below the ISM value (e.g., Favre et al 2013). These results are consistent with the results from Zhang et al (2020) for three Class I disks in Taurus (including TMC1A) but not with the order-of-magnitude depletion found by Bergner et al (2020) for two Class I disks in Serpens. For H 2 CO, the abundance ranges between ∼3×10 −10 and ∼8×10 −9 in the different sources, except for TMC1A, where the abundance is ∼5×10 −11 , probably due to the absence of emission in the inner region.…”
Section: O and H 2 Co Column Densities And Abundancessupporting
confidence: 87%
See 1 more Smart Citation
“…The derived C 17 O abundances are thus within a factor of 5 of the ISM abundance, suggesting that no substantial processing has happened, as observed for Class II disks where the CO abundance can be 2 orders of magnitude below the ISM value (e.g., Favre et al 2013). These results are consistent with the results from Zhang et al (2020) for three Class I disks in Taurus (including TMC1A) but not with the order-of-magnitude depletion found by Bergner et al (2020) for two Class I disks in Serpens. For H 2 CO, the abundance ranges between ∼3×10 −10 and ∼8×10 −9 in the different sources, except for TMC1A, where the abundance is ∼5×10 −11 , probably due to the absence of emission in the inner region.…”
Section: O and H 2 Co Column Densities And Abundancessupporting
confidence: 87%
“…Since the 2-3 Myr old disks in Lupus and Cha I show CO depletion by a factor of 10-100 (Ansdell et al 2016), these results suggest that the CO abundance decreases by a factor of 10 within 1 Myr. On the other hand, Bergner et al (2020) found C 18 O abundances a factor of 10 below the ISM value in two Class I sources in Serpens.…”
Section: Introductionmentioning
confidence: 83%
“…9 summarizes our results of the carbon abundance in the outer disk compared to the inner disk. We added TW Hya (Zhang et al 2019;Kama et al 2016b;McClure et al 2020), HD 163296 (Kama et al 2015Zhang et al 2019) and HD 100546 (Kama et al 2015(Kama et al , 2016b) and a combined point for ten Class 0/I sources (Harsono et al 2014;Zhang et al 2020b;Bergner et al 2020) to the figure for reference. These three sources are the only other sources for which the carbon abundance is determined in both the inner disk and outer disk.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, changes in the C/O ratio as a result of pebble transport may also reflect changes in the CO/H 2 , which is approximately a few times 10 −4 in the interstellar medium (ISM). In models that include pebble transport (Öberg & Bergin 2016;Krijt et al 2020), molecular CO is depleted by one to two orders of magnitude in the outer disk, which is indeed seen in spatially resolved CO isotopolog observations (Schwarz et al 2016(Schwarz et al , 2019Zhang et al 2019) and is shown to happen in the transition between the protostellar and the protoplanetary disk phase (Zhang et al 2020;Bergner et al 2020). As the mixture of ices that are most affected by this depletion process (e.g., H 2 O, CO 2 , CO) is overall oxygen-rich, this process can result in outer disk surface layers with C/O > 1 in the gas phase (Krijt et al 2020;Bosman et al 2021).…”
Section: Introductionmentioning
confidence: 70%